Stem cells in Dentistry: knowledge and attitude of Nigerian Dentists - Sede, Matthew Asizide (BioMed Central, 2013)
BACKGROUND: Several controversies exist about the methods of harvesting and eventual utilization of stem cells in Medicine and Dentistry. The objective of the study was to investigate the awareness, attitude and knowledge of the use of stem cells in Dentistry among Nigerian Dentists. METHODS: This descriptive, cross-sectional study was conducted among dentists selected from both private and public health sectors, in some of the major cities in Nigeria. RESULTS: The majority of the participants were ≤35 years in age, male, Pentecostal Christians, possessed a postgraduate qualification, had practiced for ≤5 years and were specialists or specializing. In this study, 153(81.0%) of the participants reported awareness about the use of stem cells in dentistry which was significantly associated with qualification and type of practice. Most of the respondents 114 (60.3%) had a poor knowledge of the use of stem cells in Dentistry. This was significantly associated with type of practice and awareness about stem cell use in dentistry but binary logistic regression showed awareness as the only determinant of knowledge. About three-quarters 142 (75.1%) of the participants exhibited positive attitude towards stem cell use. This had a positive non-significant association with knowledge and reported awareness. CONCLUSION: Data from this study revealed a high level of awareness, positive attitude to and poor knowledge of the use of stem cells in Dentistry among a cross section of Nigerian Dentists.